Brown Spider Venom Phospholipase-D Activity upon Different Lipid Substrates - Chaves-Moreira, Daniele; Gremski, Luiza Helena; de Moraes, Fábio Rogério [UNESP]; Vuitika, Larissa; Wille, Ana Carolina Martins; Hernández González, Jorge Enrique [UNESP]; Chaim, Olga Meiri; Senff-Ribeiro, Andrea; Arni, Raghuvir Krishnaswamy [UNESP]; Veiga, Silvio Sanches (MDPI, 2023)
Brown spider envenomation results in dermonecrosis, characterized by an intense inflammatory reaction. The principal toxins of brown spider venoms are phospholipase-D isoforms, which interact with different cellular membrane components, degrade phospholipids, and generate bioactive mediators leading to harmful effects. The Loxosceles intermedia phospholipase D, LiRecDT1, possesses a loop that modulates the accessibility to the active site and plays a crucial role in substrate. In vitro and in silico analyses were performed to determine aspects of this enzyme’s substrate preference. Sphingomyelin d18:1/6:0 was the preferred substrate of LiRecDT1 compared to other Sphingomyelins. Lysophosphatidylcholine 16:0/0:0 was preferred among other lysophosphatidylcholines, but much less than Sphingomyelin d18:1/6:0. In contrast, phosphatidylcholine d18:1/16:0 was not cleaved. Thus, the number of carbon atoms in the substrate plays a vital role in determining the optimal activity of this phospholipase-D. The presence of an amide group at C2 plays a key role in recognition and activity. In silico analyses indicated that a subsite containing the aromatic residues Y228 and W230 appears essential for choline recognition by cation-π interactions. These findings may help to explain why different cells, with different phospholipid fatty acid compositions exhibit distinct susceptibilities to brown spider venoms.
Keywords: brown spider; Loxosceles intermedia; phospholipase-D substrate; phospholipids; recombinant toxin; venom